2007
DOI: 10.1093/aob/mcm168
|View full text |Cite
|
Sign up to set email alerts
|

From Avicennia to Zizania: Seed Recalcitrance in Perspective

Abstract: There appears to be little taxonomic relationship among species exhibiting the phenomenon of seed recalcitrance, suggesting that it is a derived trait, with tolerance having been lost a number of times. Although recalcitrant seededness is best represented in the mesic tropics, particularly among rainforest climax species, it does occur in cooler, drier and markedly seasonal habitats. The selective advantages of the trait are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
296
0
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(320 citation statements)
references
References 117 publications
(201 reference statements)
8
296
0
16
Order By: Relevance
“…Substantial changes in the structure and organisation of cells occur in the late stages of dry matter accumulation and maturation drying PAMMENTER, 2008;KOSTER, 2007). Upon the beginning of drying, various mechanisms of differential expression of genes are activated that culminate in the expression and activity of important enzymes that are used in the process of tolerance acquisition RAMANJULU;BARTELS, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial changes in the structure and organisation of cells occur in the late stages of dry matter accumulation and maturation drying PAMMENTER, 2008;KOSTER, 2007). Upon the beginning of drying, various mechanisms of differential expression of genes are activated that culminate in the expression and activity of important enzymes that are used in the process of tolerance acquisition RAMANJULU;BARTELS, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Desiccation tolerance seems to be mediated by protective systems that prevent the lethal damage of different cellular components such as membranes, proteins and the cytoplasm. Three important systems have been characterised: the conversion of reducing sugars into non-reducing, long-chain sugars; the ability to prevent, tolerate or repair ROS attack by enzymatic and non-enzymatic mechanisms; and the induction of "late embryogenesis accumulated" (LEA) proteins and resistance to thermal shock (BERJAK; PAMMENTER, 2008;LI;SUN, 1999;KERMODE;FINCH-SAVAGE, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (1993), for example, suggested that the diaspores of Eugenia involucrata should be submitted to shade drying techniques after the fruit has been pulped, but observed that only nondehydrated diaspores maintained their viability after a 120-day storage. As a matter of fact, lowering water content has proved to be deleterious for a range of recalcitrant seeds, declining their storage lifespan at this 'subimbibed' condition (Berjak and Pammenter 2008 and references therein). Seeds of many Brazilian tropical tree species in the genus Eugenia (Myrtaceae) show high water content at shedding and have been considered to be sensitive to desiccation.…”
Section: Introductionmentioning
confidence: 99%
“…According to Berjak and Pammenter (2008), the best way to maintain the viability of the seed is to keep it at a low temperature and reducing contamination with fungi. As the seeds of Trichilia dregeana that can be stored several months at a temperature of 16 ºC (Goveia et al 2004), seed T. emetica and T. occidentalis (Ajayi et al 2006) kept at a temperature of 6 ºC.…”
Section: Moisture Content Decrease and Storagementioning
confidence: 99%